Neurasthenia, Civilisation and the Crisis of Spanish Manhood, c. 1890–1914 (Theatrum historiae, 2021)
In the early 1880s, a new disease called neurasthenia gained prominence within Western medicine. Neurasthenia, or nervous exhaustion, was associated with the development of modern civilisation, presented as both a cause and a consequence thereof. This article analyses the ambivalent discourse that Spanish physicians articulated about neurasthenia in relation to the status of Spanish civilisation. It places neurasthenia within the context of the wider discourse of crisis and change known as Regenerationism, presenting the argument that the diagnosis could be considered either validating or destructive, depending on whether the patient’s attitude corresponded to or diverged from the values that the Spanish elites identified as necessary for the progress of the nation. Its main symptoms of aboulia and psychic passivity made it a condition that reflected the larger crisis of national identity in the wake of the loss of the last overseas colonies to the USA in 1898. As such, it argues that the disease served to define the parameters of proper bourgeois masculinity at a time when the status of Spain’s degree of civilisation was being questioned by the country’s elites.
Keywords: neurasthenia; civilisation; bourgeoisie; masculinity; regeneracionismo; fin de siècle